2016
DOI: 10.3390/s16111863
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Affinity Biosensors Based on Disposable Screen-Printed Electrodes for Detection of Food Allergens

Abstract: Food allergens are proteins from nuts and tree nuts, fish, shellfish, wheat, soy, eggs or milk which trigger severe adverse reactions in the human body, involving IgE-type antibodies. Sensitive detection of allergens in a large variety of food matrices has become increasingly important considering the emergence of functional foods and new food manufacturing technologies. For example, proteins such as casein from milk or lysozyme and ovalbumin from eggs are sometimes used as fining agents in the wine industry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 111 publications
(220 reference statements)
0
46
0
Order By: Relevance
“…Food allergy, a type of adverse reaction to food, dependent on the susceptibility of the host, is produced by an immunological mechanism resulting from ingestion, contact or inhalation of certain substances presented in food known as allergens (mainly proteins from nuts and tree nuts, fish, shellfish, wheat, soy, eggs or milk [85]). Since the contact with food processing surfaces or sharing food utensils could constitute inadvertent routes of oral exposure to allergens, it is highly recommended to perform allergen screening, apart from food, in sanitation activities.…”
Section: Electrochemical Affinity Biosensors For Allergensmentioning
confidence: 99%
See 3 more Smart Citations
“…Food allergy, a type of adverse reaction to food, dependent on the susceptibility of the host, is produced by an immunological mechanism resulting from ingestion, contact or inhalation of certain substances presented in food known as allergens (mainly proteins from nuts and tree nuts, fish, shellfish, wheat, soy, eggs or milk [85]). Since the contact with food processing surfaces or sharing food utensils could constitute inadvertent routes of oral exposure to allergens, it is highly recommended to perform allergen screening, apart from food, in sanitation activities.…”
Section: Electrochemical Affinity Biosensors For Allergensmentioning
confidence: 99%
“…Nowadays, food allergy is considered a problem of public-health relevance with the main concern being the unintentional exposure of allergic consumers to the offending ingredient through allergen containing food. It affects 2%-3% of adults and up to 10% of children in industrialized countries with the majority of allergies persisting through lifetime [85]. Since there is no cure for allergies yet, the strict elimination of allergens from the diet and the availability of reliable and fast methods for detection and quantification of food allergens are the only options to ensure compliance with food labeling and improve consumer protection [86].…”
Section: Electrochemical Affinity Biosensors For Allergensmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported the electrochemical sensing of IgE [4][5][6][7][8][9][10][11][12][13][14][15][16], with C, Pt, and Au being employed as electrode materials for the screen-printed electrochemical transducers used in allergen detection. Subsequent modification and functionalization of these materials was therefore aimed at promoting faster charge transfer, the stable attachment of bioreceptors, and enhancing the loading capacity of biomolecules.…”
Section: Introductionmentioning
confidence: 99%